2023
DOI: 10.3390/en16062644
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Influence of Low Density Polyethylene, Novolac, and Coal Tar Pitch Additives on the Decrease in Content of Impurities Emitted from Densified Pea Husks during the Process of Their Pyrolysis

Abstract: The course of pyrolysis of pea husks was studied. It was stated that the compaction of a sample during its pyrolysis causes an almost two-fold increase in the content of hydrocarbons in the composition of volatile products in the temperature range of 350–470 °C. Low density polyethylene (LDPE), novolac, and coal tar pitch (CTP) wastes were added to feedstocks in the amount of 2 wt% in order to decrease the contribution of saturated and unsaturated hydrocarbons along with oxygen-containing compounds in volatile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…Under the influence of additives, the reflexes from Mg(OH) 2 and sharp peaks from SiO 2 disappear (Figure 11a). In a similar way, the modification of inorganics takes place under the influence of additives from plastic waste [12].…”
Section: The Investigation Of Chars Of Ph CC and Si Samples And Their...mentioning
confidence: 96%
See 1 more Smart Citation
“…Under the influence of additives, the reflexes from Mg(OH) 2 and sharp peaks from SiO 2 disappear (Figure 11a). In a similar way, the modification of inorganics takes place under the influence of additives from plastic waste [12].…”
Section: The Investigation Of Chars Of Ph CC and Si Samples And Their...mentioning
confidence: 96%
“…Moreover, the synergistic interaction between the components of blends affects the mechanism of reactions taking place during co-pyrolysis [8][9][10][11]. The thermogravimetric analysis data showed that a separate decomposition of the materials of two types in the composition of blends is observed during the co-pyrolysis of biomass with plastics [2,12]. Plastics undergo active thermal decomposition at temperatures higher than those of biomass.…”
Section: Introductionmentioning
confidence: 99%